Venom gland transcriptomics for identifying, cataloging, and characterizing venom proteins in snakes. (January 2015) - Brahma, Rajeev Kungur; McCleary, Ryan J.R.; Kini, R. Manjunatha; Doley, Robin
Abstract: Snake venoms are cocktails of protein toxins that play important roles in capture and digestion of prey. Significant qualitative and quantitative variation in snake venom composition has been observed among and within species. Understanding these variations in protein components is instrumental in interpreting clinical symptoms during human envenomation and in searching for novel venom proteins with potential therapeutic applications. In the last decade, transcriptomic analyses of venom glands have helped in understanding the composition of various snake venoms in great detail. Here we review transcriptomic analysis as a powerful tool for understanding venom profile, variation and evolution.